Pengaruh Peran Komite Audit, Reputasi Akuntan Publik dan Opini Audit Terhadap Auditor Switching Secara Voluntary - Fadhillah Raudhatul Jannah; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to examine the influence of the role of the audit committee, public accountant reputation and audit opinion on voluntary auditor switching in financial sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. This research is quantitative research. The sampling technique uses purposive sampling. The number of samples during the research year amounted to 92 data. The statistical method used is logistic regression analysis. The research results show that the role of the audit committee and audit opinion do not have a significant effect, but the reputation of public accountants has a negative effect on voluntary auditor switching in financial sector companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2022 period.